Vitrectomy for the Management of Vitreous Hemorrhage : Clinical Characteristics and Surgical Outcomes - Elvioza; Switania, Astriviani; Girsang, Waldensius; Soedarman, Soefiandi; Agustiawan, Referano (Majalah Oftalmologi Indonesia, 2023)
Purpose: Vitreous hemorrhage (VH) can cause sudden loss of vision. Conservative management is sometimes employed, yet potential risk due to delayed diagnosis and definitive treatment is concerning. Vitrectomy for VH can reduce such risk by confirming the etiology and providing surgical treatment. This study was conducted to evaluate the clinical characteristics and surgical outcomes of vitrectomy for VH in our center. Methods: A descriptive study was conducted. Data were collected retrospectively from patient’s medical records who underwent vitrectomy for VH from January to December 2020, including pre-operative clinical characteristics, surgical and adjunctive intervention, and postoperative findings. Statistical analysis was conducted. Comparison of final visual acuity to baseline visual acuity was analyzed. Results: There were 164 eyes from 164 subjects who underwent vitrectomy due to VH included in this study. The mean age of the subjects was 55,2 ± 9,8 years. Most of the subjects had severe VH pre-operatively (84,7%). Diabetic retinopathy was the most common etiology (45,1%), followed by breakthrough from submacular hemorrhage (29,9%) and retinal vein occlusion (10,3%). Most of the subjects (87,2%) underwent early vitrectomy. Final visual acuity in all subject groups improved significantly compared to baseline visual acuity (p = 0,00; p < 0,05). Final visual acuity in subjects with breakthrough from submacular hemorrhage was lower compared to other etiology. Complications after vitrectomy were recurrent VH (10,3%) and increased intraocular pressure associated with silicone oil (1,82%). Conclusion: Early vitrectomy appears to be beneficial for VH. Visual acuity varies regarding the etiology, nevertheless, was maintained or improved in most subjects.